The Multimerization of Hantavirus Nucleocapsid Protein Depends on Type-Specific Epitopes - Yoshimatsu, Kumiko (American Society for Microbiology, 2003)
Multimerization of the Hantaan virus nucleocapsid protein (NP) in Hantaan virus-infected Vero E6 cells was observed in a competitive enzyme-linked immunosorbent assay (ELISA). Recombinant and truncated NPs of Hantaan, Seoul, and Dobrava viruses lacking the N-terminal 49 amino acids were also detected as multimers. Although truncated NPs of Hantaan virus lacking the N-terminal 154 amino acids existed as a monomer, those of Seoul and Dobrava formed multimers. The multimerized truncated NP antigens of Seoul and Dobrava viruses could detect serotype-specific antibodies, whereas the monomeric truncated NP antigen of Hantaan virus lacking the N-terminal 154 amino acids could not, suggesting that a hantavirus serotype-specific epitope on the NP results in multimerization. The NP-NP interaction was also detected by using a yeast two-hybrid assay. Two regions, amino acids 100 to 125 (region 1) and amino acids 404 to 429 (region 2), were essential for the NP-NP interaction in yeast. The NP of Seoul virus in which the tryptophan at amino acid number 119 was replaced by alanine (W119A mutation) did not multimerize in the yeast two-hybrid assay, indicating that tryptophan 119 in region 1 is important for the NP-NP interaction in yeast. However, W119A mutants expressed in mammalian cells were detected as the multimer by using competitive ELISA. Similarly, the truncated NP of Seoul virus expressing amino acids 155 to 429 showed a homologous interaction in a competitive ELISA but not in the yeast two-hybrid assay, indicating that the C-terminal region is important for the multimerization detected by competitive ELISA. Combined, the results indicate that several steps and regions are involved in multimerization of hantavirus NP.